Steroid receptor coactivators – their role in immunity - Gilad, Yosi; Lonard, David M.; O’Malley, Bert W. (Frontiers in Immunology, 2022)
Steroid Receptor Coactivators (SRCs) are essential regulators of transcription with a wide range of impact on human physiology and pathology. In immunology, SRCs play multiple roles; they are involved in the regulation of nuclear factor-κB (NF-κB), macrophage activity, lymphoid cells proliferation, development and function, to name just a few. The three SRC family members, SRC-1, SRC-2 and SRC-3, can exert their immunological function either in an independent manner or act in synergy with each other. In certain biological contexts, one SRC family member can compensate for lack of activity of another member, while in other cases one SRC can exert a biological function that competes against the function of another family counterpart. In this review we illustrate the diverse biological functionality of the SRCs with regard to their role in immunity. In the light of recent development of SRC small molecule inhibitors and stimulators, we discuss their potential relevance as modulators of the immunological activity of the SRCs for therapeutic purposes.